SOFTWARE QUALITY MEASUREMEN AND METRICS (REVIEW SOME ARTICLES) - Ramadiani Ramadiani (Mulawarman University, 2012)
Software development processes have less variability than the projects or products upon which they are applied, a feature that has provided the source for considerable debate on how to capture and describe software processes for the purposes of understanding or inclusion within Software Engineering Environments. The software measurement is potentially very diverse in nature, there are four basic stages of formulation, collection, analysis and interpretation The successful measurement programmes must support the collection of cost, duration and quality values. There are some varian measurement metrics such as; performance analysis, deliverable analyses, quality objectives, schedule analyses, effort analyses etc.